Legal Protection for Tourists Against Illegal Levies in the Tourism Sector: A Socio-Legal Study of the Mandalika Special Economic Zone, Central Lombok Regency - Ahmad Rifai; Gusti Ayu Ratih Damayanti; Hafizatul Ulum; Sukarno Sukarno; Miftahul Janah; Zahwil Arham (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
Levies at tourist destinations are legally recognized as official retribution, including business service retribution under Article 88 paragraph (3) of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. However, the implementation of parking and entrance fees in the Mandalika Special Economic Zone (SEZ), Central Lombok Regency, remains problematic. Tourists have reported excessive fees, unclear parking tickets, and charges that do not comply with applicable regulations, indicating inadequate protection of tourists’ rights to transparency, security, comfort, and legal protection. This study aims to analyze the implementation of legal protection for tourists in the Mandalika SEZ and identify obstacles and appropriate solutions for strengthening such protection. This study employs an empirical legal method. Data were obtained through field observations, interviews with relevant stakeholders, and document studies, and were analyzed qualitatively. The findings indicate that legal protection for tourists remains weak. Tourists frequently receive insufficient information regarding applicable tariffs and may face coercive or unreasonable charges. Weak coordination and overlapping responsibility among tourism managers and local authorities also contribute to ineffective supervision and enforcement. This study contributes an empirical perspective on tourist protection in the Mandalika SEZ and proposes stronger coordination among the Central Lombok Regional Government, Tourism Office, Transportation Office, and ITDC, accompanied by firm sanctions against unauthorized parking attendants and transparent levy management.